Are dingoes a trophic regulator in arid Australia? A comparison of mammal communities on either side of the dingo fence - LETNIC, MIKE; KOCH, FREYA (Austral ecology, 2010)
The direct and indirect interactions that large mammalian carnivores have with other species can have far-reaching effects on ecosystems. In recent years there has been growing interest in the role that Australia's largest terrestrial predator, the dingo, may have in structuring ecosystems. In this study we investigate the effect of dingo exclusion on mammal communities, by comparing mammal assemblages where dingoes were present and absent. The study was replicated at three locations spanning 300 km in the Strzelecki Desert. We hypothesized that larger species of mammal subject to direct interactions with dingoes should increase in abundance in the absence of dingoes while smaller species subject to predation by mesopredators should decrease in abundance because of increased mesopredator impact. There were stark differences in mammal assemblages on either side of the dingo fence and the effect of dingoes appeared to scale with body size. Kangaroos and red foxes were more abundant in the absence of dingoes while Rabbits and the Dusky Hopping-mouse Notomys fuscus were less abundant where dingoes were absent, suggesting that they may benefit from lower red fox numbers in the presence of dingoes. Feral cats and dunnarts (Sminthopsis spp.) did not respond to dingo exclusion. Our study provides evidence that dingoes do structure mammal communities in arid Australia; however, dingo exclusion is also associated with a suite of land use factors, including sheep grazing and kangaroo harvesting that may also be expected to influence kangaroo and red fox populations. Maintaining or restoring populations of dingoes may be useful strategies to mitigate the impacts of mesopredators and overgrazing by herbivores.